2007
DOI: 10.1007/s00128-007-9204-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Heavy Metals on the Carbohydrate and Phenolics in Mangrove, Aegiceras corniculatum L., Seedlings

Abstract: Mangrove forest, a complex intertidal ecosystem distributed in the tropics and subtropics, appear to possess a remarkable capacity to retain heavy metals (Badarudeen et al. 1996;Machado et al. 2002;Alongi et al. 2004). Recently, mangrove forests have been shown to play an important role in the biogeochemistry of trace metal contaminants in tropical coastal areas, and are considered to have the capacity to act as a sink or buffer and to remove or immobilize heavy metals before they reach nearby aquatic ecosyste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 31 publications
3
18
0
5
Order By: Relevance
“…However, they revealed an opposite Zinc presented a moderate positive correlation with flavonoids and hydrolysable tannin levels. Similar effects were observed for condensed tannins in seedlings of Aegiceras corniculatum (Guangqiu et al, 2007) and for flavonoids in roots of Medicago sattiva (Parry et al, 1994). However, Manthey et al (2000) found that in citrus leaves the flavonoid concentration increased with zinc-deficiency.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…However, they revealed an opposite Zinc presented a moderate positive correlation with flavonoids and hydrolysable tannin levels. Similar effects were observed for condensed tannins in seedlings of Aegiceras corniculatum (Guangqiu et al, 2007) and for flavonoids in roots of Medicago sattiva (Parry et al, 1994). However, Manthey et al (2000) found that in citrus leaves the flavonoid concentration increased with zinc-deficiency.…”
Section: Resultssupporting
confidence: 66%
“…On the other hand, several works have reported the involvement of Cu and Mn in the shikimic acid pathway leading to the biosynthesis of several phenols, such as flavonoids, tannins, and lignin (Santiago et al, 2000;Diaz et al, 2001;Loponen et al, 2001;Lin et al, 2005;Guangqiu et al, 2007). Moreover, it is known that Cu and Mn influence the activity of many cellular enzymes, such as phenylalanine ammonia-lyase (PAL) (Santiago et al, 2000;Kováčik & Klejdus, 2008;Treutter, 2010), peroxidases (Diaz et al, 2001, Lin et al, 2005, Gross, 2008Kováčik et al, 2009), laccases (Lin et al, 2005), and shikimate dehydrogenase (Diaz et al, 2001, Kováčik et al, 2009.…”
Section: Resultsmentioning
confidence: 99%
“…25 A dose-response effect of copper on foliar tannins has been reported in seedlings of Aegiceras corniculatum (L.) Blanco (Myrsinaceae). 24 At first tannins decreased with an increase in copper supply; however, when copper reached toxic levels the tannin concentration also increased. These results show that the biosynthesis of phenolic compounds is dependent on Cu and Mn levels: lignification is inhibited in deficient tissues and the production of other phenolics is enhanced, which is probably the case of cluster I.…”
Section: Resultsmentioning
confidence: 97%
“…21 Several studies have reported the involvement of Cu and Mn in the shikimic acid pathway leading to the biosynthesis of several phenols, such as flavonoids, tannins, and lignin. 23,24 In plants with copper and manganese deficiency, lignification is impaired and phenolics accumulate in plant tissues. 25 A dose-response effect of copper on foliar tannins has been reported in seedlings of Aegiceras corniculatum (L.) Blanco (Myrsinaceae).…”
Section: Resultsmentioning
confidence: 99%
“…The potency of Pb in the environment influences accumulation of Pb in mangrove vegetation. The accumulation of Pb in mangrove vegetation show that mangrove has capacity to retain heavy metals (Machado et al, 2002;Alongi et al, 2004), has highly depend on the chemical (Guangqiu et al, 2007), biological and/or physical processes, and the entire soilplant-water system in mangrove ecosystem (Munawar dan Rina, 2004). Based on data of this accumulation showed mangrove vegetation had good tolerance of Pb contaminant similar with Parvaresh et al, (2011) reported the potency of Pb in the sediments and leaves of grey mangrove (A.marina), and high tolerance of mangrove vegetation in pollution area (Marchand et al, 2006).…”
Section: Hilmi Et Al 2017 Lead (Pb) Distribution On Soil Water Anmentioning
confidence: 99%